Prevalence and factors associated with condom use among people living with HIV/AIDS in Bayelsa state, Nigeria - Ofurum, Ifeoma. C. (British Journal of Healthcare and Medical Research, 2023)
Epidemiological and laboratory studies have demonstrated that latex condoms effectively prevent HIV and other sexually transmitted diseases. However, inconsistent use or nonuse of condoms among people living with HIV/AIDS (PLWHAs) could propagate the spread of infection. The aim of the study was to determine the prevalence of condom use and identify the associated factors among PLWHAs in Bayelsa state, Nigeria. Six hundred (600) participants were recruited for this cross-sectional study from the HIV clinics at Federal Medical Centre (FMC), Yenagoa, and Otuasega Cottage Hospital, Ogbia in Bayelsa State, Nigeria after giving informed consent. An interviewer-administered questionnaire was used to collect data comprising socio-demographic characteristics, condom use and ART status of the respondents. The data obtained were analyzed and presented as frequencies and percentages. Chi-square and Binary logistic regression were used to test the association between variables with statistical significance set at p<0.05. Results showed a mean age of 34.6±6.4 years, comprising 160 males (26.7%) and 440 females (73.3%). The prevalence of condom use was 69.2%. There were statistically significant associations between age (X2=7.305, P=0.007), sex (X2=7.919, P=0.005; OR=1.6 (1.1-2.4), P=0.033), religion (X2=12.238, P=0.007; OR=2.7(1.1-6.8), P=0.039), having skipped medication (X2=22.295, P<0.001; OR=2.1 (1.5-3.2), P<0.001), revealed status to someone (X2=12.002, P=0.001; OR=2.7 (1.2-6.2), P=0.020) and number of sexual partners (X2=14.684, P<0.001; OR=3.0 (1.7-5.4), P<0.001) with condom use. In conclusion, condom use among PLWHAs in Bayelsa state is sub-optimal. There is a need to explore measures that target these factors to promote the attainment of the optimal prevalence of condom use among PLWHAs.